Statistics of speech-teaching in American schools for the deaf for the year 1901 : gathered by the American Association to promote the Teaching of Speech to the Deaf; and reprinted from the tables published in the Association Review, Vol. III, No. 3. - American Association to promote the Teaching of Speech to the Deaf (Mount Airy : American Association to promote the Teaching of Speech to the Deaf, 1901)
Statistieken wat betreft het dovenonderwijs in de Verenigde Staten van Amerika, waarin o.a. een interessante opsomming van alle dovenscholen die op dat moment aanwezig waren in de VS.